Individual-Level Determinants of Employee Shirking - Judge, Timothy; Chandler, Timothy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
Employee shirking, where workers give less than full effort on the job, has typically been investigated as a construct subject to organization-level influences. Neglected are individual differences that could explain why employees in the same organization or work-group might shirk. Using a sample of workers from the health care profession in the United States, the present study sought to address these limitations by investigating subjective well-being (a dispositional construct), job satisfaction, as well as other indiuidual-level determinants of shirking. Results indicate that whites shirk significantly more than nonwhites, and that subjective well-being, job satisfaction, and age have significant, negative effects on shirking. The implications of these results are discussed.